(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This study goals to evaluate the pollution loads of contaminated dust fallen in areas near the oil refinery in Al-Shaibah area and areas around it in Basrah, Iraq between June 2011 and November 2012 in nine stations. Trace elements in dust under study are: (1.chromium Cr, 2.cadmium Cd, 3.nickel Ni and 4.lead Pb). Chronic daily intake CDI for these trace elements through (a.ingestion, b.inhalation and c.dermal contact) is calculated, (the total non-carcinogenic hazard quotient HI) and (the total carcinogenic risk TCR) are calculated. The order of non-carcinogenic hazard quotient for trace elements in dust is: (Cr > Pb > Cd > Ni). Carcinogenic risk order for trace elements in dust is: (Cr > Cd > Pb > Ni), study area is in safe of non-carcinogenic and carcinogenic impact on human health. Finally the ecological risk is evaluated in two indices: integrated pollution level in the environment Cdeg and potential ecological risk RI. The order of RI for trace elements is: (Pb > Cd > Ni > Cr), this study indicates that all stations have low "potential ecological risk".